Pendeteksi Kesesuaian Format Laporan Skripsi dengan Panduan Penulisan menggunakan Machine Learning - Eko Travada Suprapto Putro Eko Travada (FKOM UNIKU, 2019)
Machine Learning is a method in artificial intelligence system that is able to model the data entered for future needs. Many applications are applied such as classifying data, predicting relationships between data, ranking data, reading data patterns, making movie thrillers and many other implementations. In this paper, we discuss the use of machine learning analysis result to detect the student's final project format whether it is in accordance with the final project guidelines or not. Based on research, it shows that the structural modeling of machine learning can be used to detect the suitability of the format both modeling separately and modeling in combination.Key Word : Text Structure, Machine Learning, Final Project Documentation